The sermons of Henry Ward Beecher: in Plymouth Church, Brooklyn : - Beecher, Henry Ward (J. B. Ford, 1870)
1st series (1868-9) -- 2d series (March-Sept., 1869) -- 3d series (Sept., 1869-March, 1870) -- 4th series (March-Sept., 1870) -- 5th series (Sept., 1870-March, 1871) -- 6th series (March-Sept., 1871) -- 7th series (Sept., 1871-March, 1872) -- 8th series (March-Sept., 1872) -- 9th series (Sept., 1872-March, 1873) -- 10th series (March-Sept., 1873)